Effect of a post-hatch lipopolysaccharide challenge in Turkey poults and ducklings after a primary embryonic heat stress. (December 2019) - Shanmugasundaram, R.; Wick, M.; Lilburn, M.S.
Abstract: The effect of embryonic thermal manipulation on the post-hatch immune response to a lipopolysaccharide (LPS) challenge was studied in Pekin ducklings and turkey poults. Commercial duck and turkey eggs were distributed among four treatments: SS-Control (37.5 °C from embryonic day [ED] 1 to 25); SS-LPS (37.5 °C from ED1 to 25 + LPS at D0 [hatch]); HH-LPS (38 °C from ED1 to 25 + LPS at D0; SH-LPS (37.5 °C from ED1 to 10 and 38 °C from ED 11 to 25 + LPS at D0). At ED16 and ED24, the egg shell temperature of the duck and turkey eggs in the HH and SH treatments were higher (P ≤ 0.01) than the SS treatment. Ducklings and poults in the HH treatment had the lowest yolk free body weight at hatch (P ≤ 0.05). At 24, 48, and 72 h post-LPS injection, ducklings and poults in the HH-LPS treatment had significantly reduced BW compared with the SS-Con treatments (P ≤ 0.05). Ducklings and poults in the SH-LPS and HH-LPS treatments had increased plasma heat shock protein 70 (HSP70) and lower splenic HSP70 mRNA amounts than the SS-LPS treatments at 24, and 48 h post-challenge (P ≤ 0.05). At 48 and 72 h, macrophage nitric oxide (NO) production in ducklings and poults in the SH-LPS and HH-LPS treatments was lower than in the SS-LPS treatments (P ≤ 0.05). Ducklings and poults in the SH-LPS treatment had increased thymocyte proliferation compared to the SS-LPS treatment at 24, 48 and 72 h (P ≤ 0.05). At 24 h, ducklings in the SH-LPS treatment had increased splenic IL-10 and reduced IFNγ and IL-6 mRNA abundance. However, both ducklings and poults in the HH-LPS treatment had increased IFNγ, and IL-10 mRNA abundance compared to the SS-LPS treatment (P ≤ 0.05). At 48 h, SH-LPS ducklings and poults had lower splenic IL-10 mRNA abundance (P ≤ 0.05) while the HH-LPS treatment resulted in comparable splenic IL-10 mRNA compared to the SS-LPS treatment (P ≥ 0.05). Ducklings and poults in the SH-LPS treatment had increased thymic and splenic CD8 + /CD4 + ratios at 24 h versus the SS-LPS treatment (P ≤ 0.05). In conclusion, embryonic thermal manipulation from ED11-25 increased extracellular HSP70 release, thymocyte proliferation and IL-10 but decreased splenic HSP70 and IFNγ mRNA amounts at 24 h post-LPS injection. This suggests that mild heat stress during the later stages of incubation could potentially prime the embryonic immune system thereby enhances the immune response as earlier than 24 h to eliminate the inflammatory response without affecting the growth performance by increase the extracellular release of HSP70 in both ducklings and poults. Continuous exposure to the small increase in temperature from ED 1–25 (HH) caused an imbalance between pro (IFNγ)- and anti-inflammatory cytokines(IL-10) which affects hatchling responses to an inflammatory challenge and increased mortality. The amount of extracellular HSP70 could potentially play an important role in modulating the immune response against inflammatory challenges. Highlights: In duck and poult embryos, increasing incubation temperature from ED11 to 25 increased yolk free body weight at hatch, increased extracellular HSP70, thymocyte proliferation and IL-10 mRNA abundance. It decreased HSP70 splenic mRNA and IFNγ mRNA abundance at 24 h post-LPS injection. This suggests temperature can effectively prime the immune system and enhance the resistance to post-hatch inflammatory challenges. Activated T cells produce IL-10 regulatory cytokines which suppress inflammation without effecting growth and decreases mortality during post hatch.